2019
DOI: 10.3390/polym11111844
|View full text |Cite
|
Sign up to set email alerts
|

Ablation Behavior of Silicone Rubber-Benzoxazine-Based Composites for Ultra-High Temperature Applications

Abstract: A novel type of silicon rubber composite with benzoxazine resins (BZs) and ZrO2 was prepared. The ablative response of the composites was investigated. The results showed that the composites with BZs had superior thermal stability and higher resides compared to the pristine composites. The linear ablation rate of the composites decreased significantly with the increase in ZrO2 content. The maximum back-face temperature of the burnt samples was no more than 100 °C for the obtained composites. Three major ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[257] Benzoxazine resins are compatible with laying up/autoclaving, [258] resin transfer molding (RTM), [257,259,260] vacuum-assisted resin transfer molding (vaRTM), [259] vacuum transfer process (VAP), [259] filament winding, [257,260] and press molding. [257,260] Polybenzoxazine composites can be applied in ablative materials, [261] including heat protection in rockets and engine nozzles. [257] Benzoxazine matrices are used in the manufacture of carbon fiber composites.…”
Section: Properties and Applications Of Benzoxazinesmentioning
confidence: 99%
“…[257] Benzoxazine resins are compatible with laying up/autoclaving, [258] resin transfer molding (RTM), [257,259,260] vacuum-assisted resin transfer molding (vaRTM), [259] vacuum transfer process (VAP), [259] filament winding, [257,260] and press molding. [257,260] Polybenzoxazine composites can be applied in ablative materials, [261] including heat protection in rockets and engine nozzles. [257] Benzoxazine matrices are used in the manufacture of carbon fiber composites.…”
Section: Properties and Applications Of Benzoxazinesmentioning
confidence: 99%
“…This result highlights the usefulness of silicone as additive in EHSM formulations. Gao and Liu [48] have proved the capability of silicone/benzoxazine resin as ablative material, with an ablation rate as low as 0.065 mm/s with a 20% resin formulation compared to 0.114 mm/s of the control sample.…”
Section: Epdm-based and Nitrile-based Heat Shielding Materialsmentioning
confidence: 99%
“…Zhang et al (2021) also found that diamine derived from furfurylamine (PDFA), when able to react with cardanol/eugenol, had a char yield of ~65% at 850 °C. The thermal stability of highly crosslinked polybenzoxazines can be also enhanced when the biobased matrix is combined with other polymers or specific fillers. As an example (Gao et al, 2019), Gao et al studied the behavior of a new silicon rubber based composite containing benzoxazine resins and ZrO 2 : the limited ablation rate (~0.11 mm/s) of the control sample was reduced to ~0.06 mm/s with a 20% resin formulation. In their work, Subramani et al (Devaraju et al, 2019), prepared polybenzoxazines-by using cardanol and furfurylamine and further hybridization with silica was considered, by means of thiol-ene click reaction, with the main aim of enhancing thermal stability and fire resistance of the reference material.…”
Section: Benzoxazinesmentioning
confidence: 99%